Rifampicin-Associated Secondary Minimal Change Disease Presenting with Nephrotic Syndrome in a Pulmonary Tuberculosis Patient. (14th April 2021) - Sathi, Satyanand; Garg, Anil Kumar; Singh, Manoj Kumar; Saini, Virendra Singh; Vohra, Devinder
Abstract : Various extraglomerular disease processes have been associated with drug-induced secondary minimal change disease (MCD). In a majority of cases, preferably, a hypersensitivity reaction appears to be involved, and in some cases, there is direct toxic effect over glomerular capillaries. There are several reports to demonstrate that rifampicin has been associated with various nephrotoxic adverse effects, but rifampicin-induced secondary minimal change disease (MCD) is very rare. Here, we report the case of a young adult male who presented with nephrotic proteinuria with bland urine sediment after one month of initiation of rifampicin treatment for pulmonary tuberculosis. The patient had no proteinuria before the start of antituberculosis treatment. Renal biopsy showed nonproliferative glomerulopathy and immunofluorescence did not show significant glomerular immune deposits. Electron microscopy showed diffuse effacement of visceral epithelial cell foot processes and did not show any presence of glomerular immune complexes and thickening of glomerular basement membrane, promoting the diagnosis of minimal change nephrotic syndrome. The patient got complete remission after discontinuation of rifampicin.